2006
DOI: 10.1093/jac/dkl478
|View full text |Cite
|
Sign up to set email alerts
|

Is continuous infusion ceftriaxone better than once-a-day dosing in intensive care? A randomized controlled pilot study

Abstract: This pilot study suggests clinical and bacteriological advantages of continuous infusion of ceftriaxone over bolus administration in critically ill patients in patients requiring 4 or more days of treatment. This sets the scene for a large multicentre double-blind randomized controlled trial to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(129 citation statements)
references
References 32 publications
3
115
0
1
Order By: Relevance
“…Clinical cure was also higher in the continuous infusion group (70% vs. 43%, p=0.037); however, there was no observed difference in survival. These observations are similar to other small non-randomized studies that reported greater clinical success rates with continuous infusion piperacillin/tazobactam, meropenem, and ceftriaxone versus that of standard infusion in critically ill patients [60][61][62]. Finally, a doubleblind, randomized controlled study of doripenem 500 mg q8h as a 4 hour prolonged infusion versus standard infusion imipenem-cilastatin in patients with ventilator-associated pneumonia demonstrated noninferiority between dosing regimens; however, clinical success against the small population of patients infected with P. aeruginosa was numerically in favor of the prolonged infusion regimen [80% (16/20) vs. 43% (6/14)] [63].…”
Section: β-Lactamssupporting
confidence: 88%
“…Clinical cure was also higher in the continuous infusion group (70% vs. 43%, p=0.037); however, there was no observed difference in survival. These observations are similar to other small non-randomized studies that reported greater clinical success rates with continuous infusion piperacillin/tazobactam, meropenem, and ceftriaxone versus that of standard infusion in critically ill patients [60][61][62]. Finally, a doubleblind, randomized controlled study of doripenem 500 mg q8h as a 4 hour prolonged infusion versus standard infusion imipenem-cilastatin in patients with ventilator-associated pneumonia demonstrated noninferiority between dosing regimens; however, clinical success against the small population of patients infected with P. aeruginosa was numerically in favor of the prolonged infusion regimen [80% (16/20) vs. 43% (6/14)] [63].…”
Section: β-Lactamssupporting
confidence: 88%
“…A 3-h infusion of meropenem was reported to give a higher TϾMIC in plasma than a bolus injection (14). In addition, several clinical studies have suggested that prolonged infusion of beta-lactams offers clinical and bacteriological advantages for critically ill patients, including those with pulmonary infections (15,21,22,26). However, little is known about the PK/PD profile of beta-lactams in bronchial ELF and how well these drugs penetrate into bronchial regions when given intravenously by prolonged infusion.…”
mentioning
confidence: 99%
“…Growing evidence suggests that optimised antibiotic dosing in severely septic patients can increase clinical cure rates and reduce mortality (6)(7)(8). To develop such dosing regimens, detailed knowledge of the antibiotic's PK is required.…”
Section: Overviewmentioning
confidence: 99%
“…Moreover, there is growing evidence which demonstrates the optimisation of antibiotic dosing in accordance with its PK/PD profile increases clinical cure rates and reduces mortality, especially in severely septic patients (6,7,(34)(35)(36)(37).…”
Section: Antibiotic Pk/pdmentioning
confidence: 99%
See 1 more Smart Citation